2021
DOI: 10.1108/ijbm-07-2020-0413
|View full text |Cite
|
Sign up to set email alerts
|

Financial well-being of customer-to-customer co-creation experience: a comparative qualitative focus group study of savings/credit groups

Abstract: PurposeThis paper aims to explore the effects of the customer-to-customer co-creation experiences of savings/credit groups in the African context and how savings/credit groups influence financial capability and enhance financial well-being.Design/methodology/approachUsing purposive sampling, a study of a total of 18 focus groups was conducted in sub-Saharan Africa. Nine urban-based savings/credit groups were drawn from across South Africa and additional nine, rural-based savings/credit groups were studied in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 81 publications
1
40
0
Order By: Relevance
“…, 2017). Cognitive and financial experiences positively influence financial satisfaction (Sithole et al. , 2021).…”
Section: Propositions and Synthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2017). Cognitive and financial experiences positively influence financial satisfaction (Sithole et al. , 2021).…”
Section: Propositions and Synthesesmentioning
confidence: 99%
“…Family composition and income are associated with the total amount of household savings (West et al, 2017). Cognitive and financial experiences positively influence financial satisfaction (Sithole et al, 2021). Resident registration status and employment type are associated with the range of financial assets, an indicator of financial well-being in China (Cui et al, 2019).…”
Section: Propositions and Synthesesmentioning
confidence: 99%
“…However, based on market performance in new services, Taghizadeh, Rahman & Marimuthu (2021) successfully examined the influence of the DART Model on value co-creation processes in a B2B context, and found that managers can improve the participation of customers in interactive processes to better understand their expectations for new services proposed. Sithole, Mort & D'Souza (2021) focused their research efforts on demonstrating that interaction becomes the cornerstone for the co-creation of valuable experiences in the financial sector, showing that organizational philosophical principles influence the DART Model variables and finding that these experiences intervene positively in improving financial well-being. It can also be observed, through the work carried out by Schiavone, Metallo & Agrifoglio (2014), that the DART Model has even reached social media, where the model is recognized as a quite valuable theoretical argument in the co-creation of new products and services, especially in the use made of the Internet (web and social networks), where the participation of different users is strategic.…”
Section: Leaves (Authors Setting Perspectives/trends)mentioning
confidence: 99%
“…Perceived competency refers to as an individual assessment of his or her ability to deal with particular challenges perceived competency more specifically in the consumer finance sector reflects once capacity to deal with the financial-service (Sorgente & Lanz, 2017). Financial selfefficacy is referred to as individuals perceived ability to handle their finances hence, so this study considered the financial efficacy as the belief of investor and capability to comprehend the level of transparency regarding broker information (Sithole, Mort, & D'Souza, 2021). According to previous literature the perceived efficacy is contingent to individual beliefs capacity of his or her to prefer a specific Risk tolerance attitude is an effective response toward broker transparency which in turn triggers financial self-efficacy judgment of investor.…”
Section: Risk Tolerance Attitude and Financial Self Efficacymentioning
confidence: 99%